There Is Opportunity in Crisis: Will Italian Universities Seize It? - Hunter, Fiona; Sparnon , Neil (International Higher Education, 2020)
In response to COVID-19, Italy was the first European country to close its universities and switch entirely to online education. This has turned into an unprecedented national experiment that is highlighting the challenges and opportunities of online education in a system with only limited prior experience.